2008
DOI: 10.2298/avb0806509n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a calmative on selected blood parameters in horses under stressful conditions

Abstract: The results of few studies on tryptophan supplementation conducted in horses are contradictory and none of these studies have shown that tryptophan is an effective calmative in horses. The objective of the present study was to determine changes in hematological parameters, plasma lactate, serum cortisol and biochemical profile, as well as the behavior of untreated and calmative treated horses under stressful conditions in order to determine the effects of the applied calmative. The study also aims to confirm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…With the exception of Visser et al (2003Visser et al ( , 2008 and Alberghina et al (2010) who observed equine behaviour when stabled, during daily exercise and in various standardised test situations most studies have typically focused on either routine observations or challenge situations. Situations previously observed include various novel object and startle tests, handling tests, learning tests, show jumping events, sound of clippers, sound of fireworks and mane pulling (Lansade et al, 2008;Peeters et al, 2013;Alenka, 2008;Noble et al, 2013;Schmidt et al, 2010;Young et al, 2012). Seaman et al (2002) pointed out that often no relationship between different types of behaviour tests can be found and concluded that this is due to different characteristics being assessed.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of Visser et al (2003Visser et al ( , 2008 and Alberghina et al (2010) who observed equine behaviour when stabled, during daily exercise and in various standardised test situations most studies have typically focused on either routine observations or challenge situations. Situations previously observed include various novel object and startle tests, handling tests, learning tests, show jumping events, sound of clippers, sound of fireworks and mane pulling (Lansade et al, 2008;Peeters et al, 2013;Alenka, 2008;Noble et al, 2013;Schmidt et al, 2010;Young et al, 2012). Seaman et al (2002) pointed out that often no relationship between different types of behaviour tests can be found and concluded that this is due to different characteristics being assessed.…”
Section: Introductionmentioning
confidence: 99%